Factors Affecting Institutional Performance: a Case of Azad Jammu Kashmir Colleges - Malik, Mushtaq Haider; Khan, Zaheer Ahmed; Irfan, Mohammad (International Journal of Engineering and Technology, 2018)
The current study examine the factors affecting colleges’ performance in Azad Jammu Kashmir, Pakistan. For this purpose, current study apply exploratory factor analysis and multiple regression analysis to investigate the impact of supervision, planning and implementation, management development, administration and leadership on the performance of colleges in Azad Jammu Kashmir, Pakistan. The results of regression analysis confirm that supervision and management development have a positive and significant impact on performance of colleges in Azad Jammu Kashmir. The value of R-square is 52.65% which confirm the variation of performance is explained by supervision, management development, planning, leadership and administration. Therefore it is recommended that these variables are helpful in predicting performance of colleges.